The winter of the dollhouse - Schlitz, Laura Amy (Candlewick Press, 2025)
On a gloomy November night, eleven-year-old Tiphany Stokes saves an old lady from collapsing in the street. An antique doll named Gretel watches them, longing for Tiph to rescue her from life in a shop window. Though none of these three characters realizes it, their worlds are about to change: Gretel will no longer be a precious prisoner. The old lady -- is she a witch? -- will discover the secret hidden in her long-neglected dollhouse. And Tiph -- whose parents rejoice that she is "never any trouble" -- will become a thief, a dog walker, an actor, and best of all, a friend.